Synthesis of copper (II) porphyrin complexes and their interaction with c-myc G-quadruplex DNA - Kunxian YANG; Jiashu CHEN; Bingbing ZHAI; Weiming CHEN; Huanglan YANG; Yufen XIAO; Juping WANG; Wenjie MEI (KeAi Communications Co., Ltd., 2021)
Objective: To synthesize copper (II) porphyrin complexes and study their interactions with c-myc G-quadruplex DNA. Methods: The 5-p-hydroxyphenyl-10, 15, 20-tris (p-methoxyphenyl) copper (II) porphyrin complex [p-HTMOPPCu (II)] was synthesized by the conventional heating method. Ultraviolet (UV) titration, fluorescence titration, fluorescence resonance energy transfer (FRET) melting point and competitive assays were used to study the interactions between p-HTMOPPCu (II) and c-myc G-quadruplex DNA. Results: The UV absorption spectrum and fluorescence spectroscopy results indicated that the complex of p-HTMOPPCu (II) bound better with c-myc G-quadruplex DNA; the FRET melting point assay, and competitive melting point assay demonstrated that p-HTMOPPCu (II) could selectively bind and stabilize c-myc G-quadruplex DNA. Conclusion: p-HTMOPPCu (II) can bind and stabilize c-myc G-quadruplex DNA and will potentially be developed into a class of small molecule inhibitors targeting c-myc G-quadruplex DNA for clinical applications in the treatment of tumors.